Regulatory compliance as fulfilment of corporate social responsibility: an interpretative textual analysis on sustainability reports of two Chinese listed agribusinesses - Xiaorui Wang (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2017)
Through a series of interpretative textual analysis on the sustainability related non-financial disclosures of two large agribusinesses in the People's Republic of China, this paper intends to reveal how these reports are used to respond to institutional and social pressures, and how the firms are engaged in the struggle to shape the social reality in a way that serves their own interests. The findings indicate that, firstly, the two sets of sustainability reports share a common understanding of 'responsibility', which refers to the very basic product quality control. And secondly, they appear to have different perceptions of "stakeholder", which is largely resulted from the different corporate nature. Both the similarities and the differences in the two sets of reports are tightly linked to the broader social and institutional settings in China.
Keywords: 650; Agribusiness; China; CSR; Disclosure; Interpretative textual analysis